Phonetic Reader Series-Mundari - Sinha, N.K. (My University, 1974)
The Phonetic Reader gives a general description of the human speech sounds and the organs of speech that produce them, a detailed description of the production of the sounds of the particular language drills to practice those sounds, the phonemic inventory, and an orthography best suited for that language. The general description of the human speech sounds introduces and explains the technical terminology.
Keywords: Mundari